Analysis of Physics University Students' Knowledge and Understanding of Thermodynamic Scientists - Ricki Angga Rizti Yovan; Intan Sumarak Ningsari; Adhelia Karunia Sukma; Yuyun Nailul Qomariah; Hasan Nuurul Hidaayatullaah (Studies in Philosophy of Science and Education, 2021)
This study aims to determine the knowledge and understanding of physics students related to thermodynamic scientists. This research method is descriptive quantitative and qualitative. Collecting data using a google form-based test instrument with 3 levels of questions on six scientist figures, namely Joseph Black, Robert Boyle, Joseph Louis Gay Lussac, Sadi Carnot, James Presscout Joule, and Gabriel Fahrenheit. The subjects of this research were students of physics at the State University of Surabaya in levels one and two who had taken basic physics courses. Based on research data, the percentage of respondents understanding related to thermodynamics, namely 12% did not know thermodynamics scientists, 24% only knew thermodynamics scientists, 40% understood the concept of thermodynamic scientists sufficiently, 24% understood the concept and could explain the concept of thermodynamic scientists findings as a whole. University students' knowledge and understanding related to thermodynamic scientists are mostly at the level of understanding. The most widely known figure of thermodynamic scientists and the concept of the most widely understood is Robert Boyle and the most unknown is Joseph Louis Gay Lussac.